Effectiveness of tissue adhesive versus conventional sutures in the closure of inguinal hernia skin incisions: a prospective randomized controlled trial - Bellad, A. P.; Pratap, Katkar Akash (International Surgery Journal, 2018)
Background: Several surgical wound closure techniques are used including conventional sutures and skin adhesive compounds. However, tissue adhesives have evolved as an improved alternative to sutures. Few data are available on the tissue adhesives in the closure of inguinal hernia skin incisions. The aim of this study was to determine the effectiveness of tissue adhesive in the closure of inguinal hernia skin incisions compared to conventional sutures. Methods: A 1-year randomized controlled trial was conducted including 60 patients with inguinal hernia. Based on closed envelope method, patients were randomly allocated into two groups: group A and B. Patients of group A underwent skin closure with cyanoacrylate glue and that of group B underwent skin closure with conventional sutures. Demographics and clinical characteristics of the patients were recorded. On postoperative day 3, the patients were evaluated for swelling, fever, redness and discharge from the wound. SPSS 20 was used to analyze the data. Chi-square test, Fisher’s exact test, and independent sample t-test were employed in the analysis of data. Results: All the patients included in the present study were men. The age of the patients ranged between 18 and 50 years in both the groups. All patients had chief complaint of swelling in the inguinal area. The clinical characteristics of the study population including sex, mean age, weight, pulse rate, systolic blood pressure, and diastolic blood pressure were comparable in group A and group B (P>0.050). The mean duration of surgery was significantly lower in group A (66.67±4.61 min) compared to group B (71.21±6.90 min; P=0.004). On Postoperative day 3, very few patients in group B had swelling (6.67% vs. 16.67%; P = 0.228), fever (6.67% vs. 16.67%; P = 0.228), discharge (6.67% vs. 16.67%; P = 0.228), and redness (6.67% vs. 10.00%; P = 0.640) than in group A. Conclusions: Tissue adhesive is superior and equally safe as compared to conventional suture in terms of duration of surgery and postoperative surgical complications. However, large studies should be conducted focusing on infection, follow-up period, and cosmesis as the outcomes.